Plutonium : A History of the World's Most Dangerous Element - Bernstein, Jeremy (Sydney New South Book, 2007)
In his new history of this complex and dangerous element, physicist Jeremy Bernstein describes the steps that were taken to transform plutonium from a laboratory novelty into the nuclear weapon that destroyed Nagasaki. This is the first book to weave together the many strands of plutonium's story, explaining not only the science but also the people involved
Include Illustrations and Index
Keywords: Plutonium History -- Plutonium -- Close Calls